(untitled) (Research, Society and Development, 2021)
Mathematics is applied in several fields of human knowledge, that is, mathematical concepts and procedures are used to solve problems in the most diverse areas of knowledge. For example, an understanding of growth functions is a necessary prerequisite for learning many concepts in epidemiological studies. With the advent of the new coronavirus, a great deal of data is generated on the number of people infected and killed. The functional analysis of these data is necessary to understand the behavior of the COVID-19 pandemic scenario. Therefore, and within this context, the aim of this article was to show how the mathematical growth functions can be used for the analysis of scientific data from the contents of high school, focusing on the number of cases of people infected with COVID-19 in Brazil. For this purpose, an exploratory quantitative survey of data imported from the Integrated Health Surveillance Platform of the Ministry of Health of Brazil was used, specifically, in the Coronavirus Panel of disease cases in 2019, updated until July 2021 and performing the adjustment of the data using the exponential, power and polynomial functions, contents worked in the subject of mathematics in high school. The Construct application was also used, which demonstrated the relevance of isolation and social distancing in the fight against COVID-19. The results showed that the power, exponential and polynomial functions can be used to study the number of cases of people infected with COVID-19. On the other hand, the polynomial function presented better fit to the data than the power and exponential functions. The use of the Construct application showed that digital games are an excellent tool to study epidemiological phenomena in high school.